MATHEMATICAL ASSESSEMENT OF CRIME DYNAMIC WITH PUBLIC EDUCATION AND POLICE INTERVATION VIA: ABC FRACTIONAL OPERATOR - Sanda, Ayuba; S. Musa, Bashir; Ajiya, Yahaya; Audu , Aminu; Zubairu, Ishiaku (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Abstract In this work, a fractional mathematical model of crime dynamic with police and public education is designed and used to access the impacts of the intervention in controlling crime spread. The model’s positivity and boundedness were established, demonstrating its epidemiological well-posture. The model’s asymptotically stable local and global states were established using the basic reproduction number that was established. When the basic reproduction number , less than unity, indicate that crime will be reduced or eliminated in the community; a reproduction number greater than unity indicates that crime will continue in the community. The model was validated using yearly data from 2002-2021, sourced from Macrotrends. The simulation of the fractional crime model combined with public education and police presence, have shown to be effective in lowering crime rates.